Characteristics of Cocoa Farming Households in the ICARE (Integrated Corporation of Agricultural Resources Empowerment) Area East Kolaka Regency - Alam, Nur; Wahab, Abdul; Herdhiansyah, Dhian; Zainuddin, Yuliani; Ma’suf, Assayuthi; Kunta, Tamrin (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2023)
The research aims to determine the characteristics of cocoa farming households in the ICARE (Integrated Corporation of Agricultural Resources Empowerment) area of East Kolaka Regency. Activities to assess the characteristics of existing cocoa farming households using a survey approach. The research results show that the characteristics of cocoa farming households in the ICARE area consist of (1) internal characteristics of cocoa farmers: (a) average farmer age 49.22 years; (b) the average farmer's formal education is 9 years; and (c) farmer experience in cocoa farming, namely around 24 to 25 years; (2) external characteristics of cocoa farmers: (a) average land ownership is 1.80 ha; (b) the maximum age of cocoa plants cultivated by farmers in Aere District is 10 years to 14 years and in Lambandia District around 42 percent of farmers cultivate them; (c) meanwhile for the Sulawesi 1 (S1) cocoa type, farmers are less cultivated; (d) the use of fertilizers, namely urea, ZA and Phonska. Pests and diseases include fruit rot disease (Phytophthora palmivora), cocoa fruit borer (Conopomorpha cramerella), cocoa fruit sucker (Helopeltis SPP); e. the number of family members owned by cocoa farmers generally consists of 4 people; (f) the condition of equipment and infrastructure owned by cocoa farmers in the ICARE area is generally still suitable for use.